METODE SOROGAN DALAM MENINGKATKAN MINAT DAN KETERAMPILAN MEMBACA KITAB KUNING SANTRI Al-AFIYAH BOGOR JAWA BARAT - Arifin, Adiyatna; ., Fakhruddin; Hajja Ristianti, Dinna (Universitas Islam Negeri Alauddin Makassar, 2022)
The most common problem for students is the difficulty in understanding the yellow book they read. Therefore, how to increase interest and reading skills in students increasingly attract attention, especially for students of Al Afiyah Citeureup by using sorogan method. The author has analyzed some general reading skills and put forward some suggestions for further increase in interest for students, especially students al afiyah from personal experience as well as the experience of the general public who have studied pesantren from several interviews of ustadz, which can help improve the competence of reading students themselves with the practice of using sorogan methods.